Best practice criteria for sustainable maintenance management of heritage buildings in Malaysia - Sodangi, M. (Elsevier Ltd, 2014)
Sustainable development and heritage conservation have become guiding principles for our modern industrial society. In order to achieve a sustainable management of heritage building conservation in Malaysia, it is vital that maintenance takes a leading role in conserving the heritage values of the buildings. However, there has been no published work on assessment of the relative importance of each best practice criteria for sustainable maintenance management of heritage buildings in Malaysia. Thus, this paper is aimed at identifying and ranking the criteria that support sustainable best practice.Data collected through questionnaire which covered a selected sample of experts in the field of heritage building conservation. Data were analyzed using Relative Importance Index (RII), Kendall's concordance test, and Pearson's Chi-Square test. The results show that maintenance staff training and expertise was the most important criterion considered crucial by the respondents in supporting sustainable best practice. The paper is a pioneering attempt at establishing the criteria that support sustainable best practice in the maintenance management of heritage buildings in developing countries like Malaysia. Â© 2014 The Authors. Published by Elsevier Ltd.